ASSESSMENT OF SANDBANK DYNAMICS USING HIGH-RESOLUTION IMAGES IN AREAL DO LIMEIRA RIVER, SOUTHERN BRAZIL - Rademann, Lucas Krein; Trentin, Romario; Robaina, Luís Eduardo de Souza; Breunig, Fabio Marcelo (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
The river deposition dynamics is determined by its transport capacity and volume of sediments available in the drainage channel. Such changes in this dynamic can be indicative of an environmental disturbance, and its assessment can assist the territorial planning, management, and ordering. Therefore, this study aims to analyze the dynamics of sandbanks in the Areal do Limeira River, between the years 2009 and 2020, by using high spatial resolution satellite images. The methodology consisted in the use of a series of RapidEye images for the visual vectorization on the image of the sandbanks in the Areal do Limeira River watershed. Subsequently, the data was tabulated, analyzed, and compared with the rainfall volume and land use aspects. There was a higher occurrence of sandbanks between 2009 and 2012, coinciding with the implementation of forestry plantations in the study area, followed by a sharp decline until 2015, and a small increase and stabilization in the following years, when the forestry plantations reached their mature stage. In general, the use of high-resolution images has allowed for the identification of fluvial sandbanks, with adequate precision and quality.